PASAR TERAPUNG DAN AREA WISATA SUNGAI DI SUNGAI KAHAYAN, PALANGKARAYA DENGAN PENDEKATAN ARSITEKTUR WATERFRONT - Yusua Salomo; Rachmadi Nugroho; Wiwik Setyaningsih (Universitas Sebelas Maret Surakarta, 2014)
Abstract: Designing Floating Market and River Tourism Area Palangkaraya background by the development banks of the areas that tend Kahajan disordered , and the vision of the city government that wants to make Palangkaraya Palangkaraya as river front city so the purpose of this scheme is to design a riparian area Kahayan to realize the government 's vision city and county make Kahayan riverbanks became more organized and can be a leading tourist attraction Palangkaraya . Design problem is how to design the Floating Market and reserve the Waterfront Architecture approach , the determination of the buoyant material , waste management and reserve Floating Market , building mass system , as well as the application of local knowledge on the design of Borneo . Designing method used is the method of architectural design . The result is the design of a waterfront area that is packed into a unique tourist area that is only found in Borneo in general and in particular Palangkaraya to represent Dayak culture in it . Keywords: Waterfront, Floating Market, River Tour, Kahayan, Palangkaraya.